2019
DOI: 10.52962/ipjaf.2019.3.1.64
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Islamic Banks in Somalia in the Post-Conflict Era: Prospects and Challenges

Abstract: Since the fall of Somalia’s central government in 1991, Somalia experienced an intractable civil war that not only undermined and devastated much of the nations’ social life but also, led to a massive collapse of the country’s financial sector. Nearly a quarter century, Somalia has no functioning financial system due to the conflict and political mayhem. Such circumstances prevented Somalia from developing an effective and coherent financial system. Following the collapse of the country’s institutions, the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Some of the Muslim countries nonetheless are yet to implement tawarruq , such as Somalia. Musse et al (2019) argued that tawarruq is needed as a mode of cash financing as the Islamic banking industry is struggling with a shortage of products for liquidity management.…”
Section: Background and Objectives Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the Muslim countries nonetheless are yet to implement tawarruq , such as Somalia. Musse et al (2019) argued that tawarruq is needed as a mode of cash financing as the Islamic banking industry is struggling with a shortage of products for liquidity management.…”
Section: Background and Objectives Of The Studymentioning
confidence: 99%
“…Tawarruq is nonetheless not currently offered in Somalia because Islamic banking in the country is still in a nascent stage of development, hence the limited products offering. QRFM 15,5 Musse et al (2019) reported that the main reasons why tawarruq is not offered in Somalia are insufficient human capital, low level of awareness of the product and Shariah issues pertaining to the product. So far, there are limited empirical studies that have been conducted in Somalia about Islamic banks, particularly tawarruq (Abdinur and Ondes, 2022).…”
mentioning
confidence: 99%
“…Islamic banks are still relatively new in Somalia and have a small amount of funding, and Islamic banks in Somalia in particular have liquidity issues (Jibril, 2020;Musse, Rashid, & Zainol, 2019). There is no method for a consumer to obtain the cash they require from a bank in Somalia since the financial sector has only recently established itself and lacks adequate liquidity management.…”
Section: Background and Objectives Of The Studymentioning
confidence: 99%
“…Tawarruq is not practiced in Somalia since the country's Islamic financial sector is still developing. As one of several products, tawarruq is not performed in Somalia for many reasons, including a lack of human resources, a lack of awareness, and potential Shariah issues (Jibril, 2020;Musse et al, 2019). To evaluate the tawarruq contract's overall applications in Somalia for cash financing, this study focuses on some different variables, including level of awareness, the need for tawarruq, compatibility, relative advantage, behavioral intention to use it, and the role of Shariah scholars (Amin, Abdul-Rahman, Ramayah, Supinah, & Mohd-Aris, 2014;Faisal, Akhtar, and Rehman, 2014;Jansson, 2011;Obeid & Kaabachi, 2016).…”
Section: Background and Objectives Of The Studymentioning
confidence: 99%
“…After the collapse of the central government in Somalia in the 1990s, the country's political and economic system collapsed due to the civil war (Musse et al, 2019). According to the World Bank (World Bank, 2020) , the Somali population estimated in 2007 at about 14 million, where 69% of the population under the poor, making the country one of the poorest countries in the world.…”
Section: Introductionmentioning
confidence: 99%